Talorchestia qeshm sp. nov., a new talitrid amphipod from the Persian Gulf (Amphipoda, Talitridae) - Lowry, Im; Momtazi, Farzaneh (Zootaxa, 2015)
A new talitrid amphipod species, Talorchestia qeshm sp. nov., is described from Qeshm Island in the south-eastern Persian Gulf. This is the westernmost confirmed record for Talorchestia and places the genus firmly in the western Indian Ocean.